TRANSFORMATIONAL LEADERSHIP OF MADRASAH PRINCIPALS BASED ON ISLAMIC VALUES: AN INTEGRATIVE MODEL FOR TEACHER COMPETENCY DEVELOPMENT IN THE DIGITAL ERA - Ratnawati, Rinta; Nursalim, Mochammad; Khamidi, Amrozi (Universitas Al-Amien Prenduan, 2025)
The rapid transformation of Islamic education in the digital era presents unique challenges for madrasah leadership in developing teacher competencies. The phenomenon of educational quality gaps between madrasah and conventional schools, particularly in technological literacy and innovative teaching methods, requires effective leadership strategies that integrate Islamic values with contemporary educational management. This study aims to analyze the transformational leadership role of madrasah principals in developing teacher competence through an Islamic values-based integrative model at Bustanuddin Galis Pamekasan Islamic Educational Institution. Employing a qualitative approach with single case study design, this six-month research utilized in-depth interviews with 20 purposively selected informants (including the principal, vice principals, subject teacher association coordinators, and teachers), participatory observation, and comprehensive document analysis of strategic plans, work programs, and professional development reports. The findings reveal that the principal successfully implements transformational leadership integrated with Islamic values (uswatun hasanah, syura, and spiritual motivation), resulting in a comprehensive teacher competency development model comprising seven key strategies: needs-based programs, in-house training, subject teacher association strengthening, mentoring systems, classroom action research, technology integration, and comparative studies. The research generates an innovative integrative model that combines professional and spiritual development aspects, demonstrating 85% improvement in teacher pedagogical competence and 78% enhancement in professional competence, contributing significantly to madrasah education quality enhancement and providing empirical evidence for Islamic educational leadership effectiveness.